Structural characterization, derivatization and antibacterial activity of secondary metabolites produced by termite‐associated Streptomyces showdoensis BYF17. Issue 5 (25th January 2023) - Huang, Zhongdi; Tang, Wei; Jiang, Taoshan; Xu, Xiaoting; Kong, Kun; Shi, Shuping; Zhang, Shuxiang; Cao, Wei; Zhang, Yinglao
Abstract: BACKGROUND: Insect‐associated Streptomyces is a valuable resource for development of compounds with antibacterial potential. However, relatively little is known of the secondary metabolites produced by termite‐associated Streptomyces. RESULTS: Here, seven compounds including o ‐acetaminophenol (1), phenazine‐1, 6‐dicarboxylic acid (2), phenylacetic acid (3), phenazinolin D (4), izumiphenazine A (5), izumiphenazine B (6) and phenazinolin E (7) were obtained from the fermentation broth of a termite‐associated Streptomyces showdoensis BYF17, which was isolated from the body surfaces of Odontotermes formosanus . Two additional novel derivative compounds (6a and 6b) were synthesized via acetylation and methylation, respectively. The structures of these compounds were elucidated by spectroscopic analyses. The antibacterial bioassay showed that compound 6a displayed strong inhibitory effects against Pseudomonas syringae pv . actinidiae (Psa), with a zone of inhibition (ZOI) diameter of 20.6 mm, which was comparable to that of positive gentamicin sulfate with a ZOI value of 25.6 mm. Furthermore, the Day 5 curative activities of both compounds 6 and 6a against kiwifruit bacterial canker were 71.5%, which was higher than those of referred oxine‐copper (55.0%) and ethylicin (46.8%) at a concentration of 200 μg mL −1 . In addition, the mechanism analysis based on scanning electron microscopic observation revealed that both compounds 6 and 6a destroyed the integrity of the Psa cell membrane. CONCLUSION: The results of biological tests showed that these bioactive compounds exhibit potent antimicrobial activities, which have the potential to be developed into new antibacterial agents. © 2023 Society of Chemical Industry. Abstract : Seven secondary metabolites and additional two derivatives were isolated and charactered from termite‐associated Streptomyces showdoensis BYF17. Some of these compounds exhibited potent antimicrobial activities. Notably, both compounds 6 and 6a displayed potent control efficiencies against kiwifruit bacterial canker, and have the potential to be developed into new antibacterial agents.